Genetic basis of offspring number–body weight tradeoff in Drosophila melanogaster. Issue 7 (20th April 2021) - Akhund-Zade, Jamilla; Lall, Shraddha; Gajda, Erika; Yoon, Denise; Ayroles, Julien F; de Bivort, Benjamin L
Abstract: Drosophila melanogaster egg production, a proxy for fecundity, is an extensively studied life-history trait with a strong genetic basis. As eggs develop into larvae and adults, space and resource constraints can put pressure on the developing offspring, leading to a decrease in viability, body size, and lifespan. Our goal was to map the genetic basis of offspring number and weight under the restriction of a standard laboratory vial. We screened 143 lines from the Drosophila Genetic Reference Panel for offspring numbers and weights to create an "offspring index" that captured the number vs weight tradeoff. We found 18 genes containing 30 variants associated with variation in the offspring index. Validation of hid, Sox21b, CG8312, and mub candidate genes using gene disruption mutants demonstrated a role in adult stage viability, while mutations in Ih and Rbp increased offspring number and increased weight, respectively. The polygenic basis of offspring number and weight, with many variants of small effect, as well as the involvement of genes with varied functional roles, support the notion of Fisher's "infinitesimal model" for this life-history trait.